2018
DOI: 10.1002/art.40386
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Cytokines Stabilize SOXC Transcription Factors to Mediate the Transformation of Fibroblast‐Like Synoviocytes in Arthritic Disease

Abstract: Objectives Fibroblast-like synoviocytes (FLS) produce key synovial fluid and tissue components to ensure joint integrity under healthy conditions, whereas they become cancer-like and aggressively contribute to joint degeneration in inflammatory arthritis. Here we asked whether the SOXC transcription factors SOX4 and SOX11, whose functions are critical in joint development and many cancer types, contribute to FLS activities under normal and inflammatory conditions. Methods We inactivated the SOXC genes in FLS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

5
3

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 49 publications
0
33
0
Order By: Relevance
“…In addition, our results indicate that Sox4 expression in hepatocytes could be regulated by glucose, palmitate, and insulin. Recent studies identified Sox4 as a downstream target of inflammatory cytokines (43,44). Therefore, whether chronic and persistent inflammation in obesity contributes to the upregulation of Sox4 remains to be addressed.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, our results indicate that Sox4 expression in hepatocytes could be regulated by glucose, palmitate, and insulin. Recent studies identified Sox4 as a downstream target of inflammatory cytokines (43,44). Therefore, whether chronic and persistent inflammation in obesity contributes to the upregulation of Sox4 remains to be addressed.…”
Section: Discussionmentioning
confidence: 99%
“…There is little doubt, however, that these proteins are subjected to posttranslational regulation. Supporting this concept, inhibition of SOXC proteasomal degradation was proposed as a major mechanism whereby inflammatory cytokines mediate synovial fibroblast transformation in arthritis (Bhattaram, Muschler, Wixler, & Lefebvre, 2018). A post-translational mechanism was postulated but remains to be identified.…”
Section: Post-translational Regulation Of Sox Proteins In Skeletal Cellsmentioning
confidence: 99%
“…The institutional animal care and use committee (IACUC) at Emory University approved animal husbandry and experimental procedures. FLS were isolated by digesting interphalangeal joint synovium according to previously described protocol (11). Hind paws from wild-type mice with a C57/B6 background were deskinned, followed by digestion with 1mg/ml collagenase IV (Sigma-Aldrich) for 2h at 37°C under sterile conditions (35).…”
Section: Methodsmentioning
confidence: 99%
“…The inflammatory milieu in RA synovium promotes an abnormal epigenetic landscape, modulates chromatin accessibility and favors the pathogenic processes observed in RA FLS such as invasion, migration and production of proinflammatory mediators (1,8,9). The vital role of tumor necrosis factoralpha (TNF) in triggering and maintaining an aggressive FLS phenotype has been well documented both in the in vivo and in vitro studies (10)(11)(12)(13). Hence, manipulating TNFinduced sustained chromatin activation in RA FLS represent a treatment opportunity that might aid in combating RA persistence and therapeutic resistance.…”
Section: Introductionmentioning
confidence: 99%